Bidding in common value fair division games - Tobias Brünner; Alice Becker (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
In a fair division game an indivisible object with an unknown common value is owned by a group of individuals and should be allocated to one of them while the others are compensated monetarily. Implementing fair division games in the lab, we fi nd many occurrences of the winner's curse under the first-price rule but only few occurrences under the second-price rule. Moreover, bidding behavior is very heterogeneous across subjects. A considerable share of our subjects anticipates that other bidders overbid and respond by bidding lower than in equilibrium. We fi nd that the level-k model performs well in explaining our results.
Keywords: D44; C91; D03; 330